"It’s just totally lawless out here": a rural green criminological exploration of foxhunting, policing, and ‘regulatory capture’ - Graham, Lynne (Criminological encounters, 2022)
Despite having been banned by the Hunting Act (2004), the practice of fox-hunting with hounds still persists on a significant scale in the UK (Agerholme, 2019). Nevertheless, foxhunting remains a relatively understudied topic within criminological research, potentially as a result of it being both an example of rural and green crime, both of which have been traditionally marginalised in mainstream criminology (Donnermeyer and DeKeseredy, 2014). In an effort to partially redress this, this paper applies the concept of ‘regulatory capture’ to the case of foxhunting, in order to explore the policing of foxhunting through a rural green criminological lens. Drawing on 43 qualitative interviews, and freedom of information requests to police forces, the paper critically examines the policing of foxhunting in rural England and Wales. The concept of ‘regulatory capture’ is useful in identifying "the process through which special interests affect state intervention in any of its forms" (Dal Bo, 2006: 203). We examine three related themes that were identified within the data, these are: the influence of industry; offenders as informers; and police who hunt. We find that regulatory capture provides a compelling potential explanation for police reluctance to address wildlife crime like foxhunting.